Saudi Arabian Government Crisis Management and Prevention Strategies: has it Been Effective to Curb the Presence of Radical Groups in the Social Media? - Alyousef, Yazeed; Zanuddin, Hasmah (International Journal of Engineering and Technology, 2018)
The role of media over the expansion of the terrorism increased since the beginning of twenty-first century. With the appearance of internet technologies and other applications including social media platforms, the terrorist raised dramatically. Over the last few years the young people of Middle East countries became victims of active presence of the ISIS and other radical groups. The representatives of terrorist organizations started promotion campaigns over these platforms with the purpose to attract more people to the promotion of their strategic goals. With that, the government of Saudi Arabia and other Middle East countries lack resources in order to limit presence of these formations in social media. This research aims to consider the effects of the use of social media by young people of Saudi Arabia over the achievement of strategic goals and priorities in reference to the living of young people and examined the Saudi Arabian government crisis management and prevention strategies effectiveness. Throughout the research, the effectiveness of separate management practices will be considered in order to prevent occurrence of damages to the life and health of young people in Saudi Arabia with improvement of the national security. The paper aims to prove that state bodies should develop and enforce relevant management practices so that to benefit to the improvement of the security of the country.Â Â